Three new species of Stiphrornis (Aves: Muscicapidae) from the Afro-tropics, with a molecular phylogenetic assessment of the genus. Issue 2 (4th March 2017) - Voelker, Gary; Tobler, Michael; Prestridge, Heather L.; Duijm, Elza; Groenenberg, Dick; Hutchinson, Mark R.; Martin, Alyssa D.; Nieman, Aline; Roselaar, Cees S.; Huntley, Jerry W.
Abstract : We describe three new species of forest robin in the genus Stiphrornis ; two from West Africa and one from the Congo Basin. Each species represents a distinct phylogenetic lineage based on genetic analysis. In addition to genetic differentiation, each new species is diagnosable from other Stiphrornis lineages by morphology, and by plumage. One of the new species appears to be restricted to the Central and Brong-Ahafo Regions of Ghana, and another is restricted to Benin and the Central Region of Ghana. In Ghana, these two new species presumably come into contact with Stiphrornis erythrothorax (Western Region of Ghana and westward), and there is evidence that one of the new species has a distinguishably different song from erythrothorax . The distribution of the third new species is primarily on the south bank of the Congo River, near the city of Kisangani. Recognition of these species provides additional evidence that Afrotropical forests are harbouring substantial cryptic diversity, and that our knowledge of the drivers of this diversity remains poorly documented across the region. http://www.zoobank.org/urn:lsid:zoobank.org:pub:BF2A0BE6-1140-4EFF-9035-380D61AB03AE